Epilepsy surgery in pediatric patients - Andrej Vranič; Natalija Krajnc (Zdravniški Vestnik, 2018)
Epilepsy surgery is a branch of functional neurosurgery, developed for treating patients with resistant epilepsy in pediatric and adult population. The etiology and clinical picture of pediatric epilepsy are very heterogeneous and patients who could benefit from surgery should be chosen very carefully. In this article we present preoperative preparation of epilepsy patients, as well as surgical techniques used in pediatric epilepsy surgery. Robotic stereoelectroencephalography (SEEG) is the most precise technique used for implanting intracranial electrodes. Epileptic foci can be excluded by resection or disconnection procedures. Hypothalamic hamartomas are most frequently treated endoscopically. The results of surgical treatment are good: about two thirds of children are seizure-free after surgery while in the rest of them we mostly achieve improvement.